"Is Christus verdeeld?" Nadenke oor die teologiese regverdiging van kerkverdeeldheid en kerkskeuring - Van Wyk, J. H. (Verbum et ecclesia, 2008)
"Is Christ divided?" Reflections on the theological justification of church disunity and church schism In this article the author investigates the question whether a church schism could ever be justified. He considers on the one hand the Biblical message on church unity and on the other hand the many justifications of church disunity (schism). He concludes that most of these justifications are unacceptable rasionalisations and that Post-Reformation theology distanced itself far away from Biblical ecclesiology in this regard.